Role of Biosynthesized Ag-NPs Using Aspergillus niger (MK503444.1) in Antimicrobial, Anti-Cancer and Anti-Angiogenic Activities - Pasha, Akbar; Kumbhakar, Divya Vishambhar; Sana, Siva Sankar; Ravinder, Doneti; Lakshmi, B. Vijaya; Kalangi, Suresh K.; Pawar, Smita C. (Frontiers in Pharmacology, 2022)
Green synthesis of nanoparticles is regarded as a safe and non-toxic process over conventional synthesis. Owing to the medicinal value of biologically derived biomolecules and utilizing them in synergy with nanoscience to offer more accurate therapeutic options to various diseases is an emerging field. One such study we present here with highlights of the synthesis and efficacy of biogenic silver nanoparticles produced from the extract of Aspergillus niger SAP2211 (accession number: MK503444.1) as an antimicrobial, anti-cancerous and anti-angiogenic agent. The synthesized Ag-NPs were characterized following UV–vis, FTIR, XRD, SEM and TEM, and were found to possess bactericidal activity against the selected pathogenic microbes, such as Staphylococcus aureus, Escherichia coli, and Salmonella typhi. Further, we evaluated cytotoxicity effect of this biogenic Ag-NPs using MMT assay on normal cardio myoblast (H9C2) and cancerous human cervical carcinoma (HeLa) cells. Doxorubicin used as positive control. This Ag-NPs have shown trivial cytotoxicity at the IC50 concentration on normal cells (IC50 = 47.17 µg/ml) over the cancer cells (IC50 = 8.609 µg/ml) with nearly 7 fold difference, indicating it as a selective anti-cancerous agent in contrast to standard drug doxorubicin (IC50 = 6.338 µg/ml). Further in-vitro assessment of wound healing capability by scratch wound healing assay, invasion by transwell matrigel invasion assay, and apoptosis via DAPI and annexin V-FITC assays were studied in HeLa cells. Synthesized biogenic Ag-NPs have shown to be anti-angiogenic in nature, which was established by in-vivo chick chorioallantois membrane assay. Overall, in vitro studies revealed that biogenic Ag-NPs positively inhibited migration, invasion, and induced apoptosis, and in-vivo CAM assay revealed that intercapillary network was reduced and the angiogenesis was inhibited.